2007
DOI: 10.1007/bf02898031
|View full text |Cite
|
Sign up to set email alerts
|

Association of thoracic kyphosis with subjective poor health, functional activity and blood pressure in the community-dwelling elderly

Abstract: Kyphosis is associated with subjective poor health in the community-dwelling female elderly in this study population, but not with functional activity and blood pressure both in males and females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
2
19
0
2
Order By: Relevance
“…Whereas, thoracic kyphosis decreased with age among men. Among women, on the contrary, thoracic kyphosis tended to increase with age as reported in other studies (2,29,31). Although we could not explain this sex difference, thoracic kyphosis might decrease as a compensation for the decrease in lumbar lordosis in men.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Whereas, thoracic kyphosis decreased with age among men. Among women, on the contrary, thoracic kyphosis tended to increase with age as reported in other studies (2,29,31). Although we could not explain this sex difference, thoracic kyphosis might decrease as a compensation for the decrease in lumbar lordosis in men.…”
Section: Discussionsupporting
confidence: 83%
“…Spinal posture changes with age, but accumulated evidence shows that continued good spinal posture is important in allowing the aged to maintain independent lives (2,3). Hirose and colleagues (4) reported that the posture of the trunk in the sagittal plane is associated not only with the distance and time parameters of gait, but also with functional performance in the elderly population.…”
mentioning
confidence: 99%
“…Ghandhari et al [23] agreed that lumbar lordosis and thoracic kyphosis are correlated, so that lumbar lordosis would increase as thoracic kyphosis increases. The thoracic kyphosis angle increases with age and the increase is greater in females than in males [24]. Similar results are recorded in the current study, regarding lumbar lordosis.…”
Section: Discussionsupporting
confidence: 90%
“…4,5 The thoracic curvature worsens with age and more in women than in men, especially. 4,6 FHP abnormally changes the anatomical structures of the cervical vertebra and thoracic vertebra according to the thoracic curvature, causing changes in the thoracic cage and lung function, that resulted to chronic musculoskeletal system pain syndrome decreases the normal muscle breathing pattern and cause neck pain. 4,7 Since the neck is the area that the respiratory assistant muscles refer to the function of the neck abnormalities affect the breathing function, 7 a severe FHP causes shortening and weakening of the respiratory muscles, resulting in low respiratory circulation function and breathing capacity, it decreases forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC).…”
Section: Introductionmentioning
confidence: 99%